2011
DOI: 10.1002/ptr.3583
|View full text |Cite
|
Sign up to set email alerts
|

7,7′′‐Dimethoxyagastisflavone‐induced Apoptotic or Autophagic Cell Death in Different Cancer Cells

Abstract: 7,7''-Dimethoxyagastisflavone (DMGF), a biflavonoid isolated from the needles of Taxus × media cv. Hicksii, was evaluated for its antiproliferative and antineoplastic effects in three human cancer cell lines. Interestingly, DMGF caused cell death via different pathways in different cancer cells. DMGF induced apoptosis, activated caspase-3 activity and changed the mitochondrial membrane potential in HT-29 human colon cancer cells. However, the apoptotic pathway is not the major pathway involved in DMGF-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…DMGF is a bioactive biflavonoid from Ouratea parviflora [ 6 ] or Taxus media var. Hicksii [ 7 ]; however, little is known about its functions in tumor angiogenesis, metastasis and tumor growth except for its effect on inducing tumor death through apoptosis or autophagy in different cancer cells [ 7 ]. In this study, the DMGF was shown to dramatically suppress the spontaneous metastasis of B16F10 melanoma cells from subcutaneous sites to the spleen (Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DMGF is a bioactive biflavonoid from Ouratea parviflora [ 6 ] or Taxus media var. Hicksii [ 7 ]; however, little is known about its functions in tumor angiogenesis, metastasis and tumor growth except for its effect on inducing tumor death through apoptosis or autophagy in different cancer cells [ 7 ]. In this study, the DMGF was shown to dramatically suppress the spontaneous metastasis of B16F10 melanoma cells from subcutaneous sites to the spleen (Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SVEC4-10 is sensitive as B16F10 cells. However, in our previous results, DMGF had different antiproliferative effects between cancer cell lines and primary cells, including human PBMCs and mouse splenocytes [ 7 ]. These results showed that DMGF has selective cytotoxicity between normal and tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some studies have reported inconclusive associations (Romagnolo and Selmin, ). Flavonoids such as quercetin (Yang, et al ., ), rutin (Marrassini et al ., ), hesperetin (Aranganathan and Nalini, ), xanthohumol (Zajc et al ., ), 7,7''‐dimethoxyagastisflavone (Hwang et al ., ), silymarin (Yu et al ., ), chrysoplenetin and chrysosplenol D (from Vitex negundo ) (Awale et al ., ), formononetin, genistein (Mansoor et al ., ), peonidin and cyaniding (two anthocyanidins) (Tanaka et al ., ) and many others isolated from a number of medicinal plants such as Marrubium thessalum (Argyropoulou et al ., ), Zeyheria montana (Seito et al ., ), Spatholobus suberectus (Shim, ) and Glycine max (Goh et al ., ), as well as related polyphenolic compounds such as rotenoids (Aviello et al ., ; Kang et al ., ), anthraquinones (Capasso et al ., ; Dibwe et al ., ; Lee et al ., , ; Aviello et al ., ) and resveratrol (Lim et al ., ) have recently been shown to exert genoprotective, cytotoxic, antiproliferative and/or proapoptotic actions in different tumoural cell lines. More in‐depth studies have shown that liquiritigenin, a flavanone found in a variety of plants including licorice, promoted apoptosis in HeLa cells, an effect associated with the up‐regulation of p53 and Bax, down‐regulation of Bcl‐2 and surviving, release of cytochrome c and elevated activity of caspase‐9 and ‐3 (Liu et al ., ).…”
Section: Introductionmentioning
confidence: 99%